Gesundheitsproblematik der Dritten Welt - Diesfeld, Hans J. (Wiss. Buchges., 1989)
Hans Jochen Diesfeld: "Gesundheitsproblematik der Dritten Welt". Wissenschaftliche Buchgesellschaft, Darmstadt 1989. 161 Seiten, 19,80 DM